Energy consumption and environmental degradation nexus: A systematic review and meta-analysis of fossil fuel and renewable energy consumption - (:unkn) unknown (My University, 2022)
This study examines the energy consumption and environmental degradation nexus at a disaggregated (i.e., fossil fuel energy and renewable energy) level by investigating bibliometric indicators on a global scale. For this purpose, the study considers a number of studies published between 1980 and 2021 that were selected on the Web of Science (WoS) database based on relevant keywords. A bibliometric analysis was done through VOS-viewer from a comparative perspective. Thus, 17,298 studies on fossil fuel energy consumption & environmental degradation and 62,002 studies on renewable energy consumption & environmental degradation were identified. Bibliometric indicators and network visualizations were used to present the results, which show: (i) the topic of disaggregated energy consumption and environmental degradation has been a problem since 1991; (ii) the number of renewable energy-related studies has exceeded the number of fossil fuel-related studies regarding environmental degradation; (iii) many of the studies in both disaggregated groups fall under the categories of energy fuels, environmental sciences, and green sustainable science technology, respectively; (iv) most of the studies have been published by Elsevier; (v) most of the researchers are from the United States of America (USA), whereas those from China and Pakistan have recently come to the fore. Hence, this study assesses the emerging trends in the literature on the energy consumption and environmental degradation nexus at a disaggregated level. Moreover, potential issues to be included by future studies are suggested.
Keywords: Tarımsal Bilimler; Çevre Mühendisliği; Çevre Teknolojisi; Ekoloji ve Kirlenme; Mühendislik ve Teknoloji; Agricultural Sciences; Environmental Engineering; Environmental Technology; Ecology and Pollution; Engineering and Technology; EKOLOJİ; Çevre / Ekoloji; Tarım ve Çevre Bilimleri (AGE); ECOLOGY; ENVIRONMENT/ECOLOGY; Agriculture & Environment Sciences (AGE); Ekoloji; Ekolojik Modelleme; Ekoloji, Evrim, Davranış ve Sistematik; Fizik Bilimleri; Yaşam Bilimleri; Ecology; Ecological Modeling; Ecology, Evolution, Behavior and Systematics; Physical Sciences; Life Sciences; Fossil fuel energy; Renewable energy; Energy consumption; Environmental degradation; Bibliometric analysis; ECONOMIC-GROWTH; CO2 EMISSIONS; CARBON EMISSIONS; KUZNETS CURVE; OIL CONSUMPTION; HYPOTHESIS; PANEL